Фотограмметрія як метод створення 3D-моделей - Клепіков, К. В.; М'ячиков, І. В. (ХНУРЕ, 2025)
This paper describes the process of creating 3D models using additional photogrammetry technologies to make the geometry of real objects. The main stages are described: shooting an object from different angles, image processing, and creating a polygonal mesh and texture. Particular attention is paid to the KIRI Engine software, which uses advanced computing algorithms to automate the 3D scanning process. Recommendations are given on optimal lighting, the number of photographs, and their processing. In addition, the article emphasizes the possibility of exporting finished models to various formats for further development in 3D editors and applications in virtual and augmented reality.
Keywords: фотограмметрія; створення 3D-моделей